Resurrecting a subgenus to genus: Molecular phylogeny of Euphyllia and Fimbriaphyllia (order Scleractinia; family Euphyllidae; clade V) - Luzon, Katrina S. (Animo Repository, 2017)
Background. The corallum is crucial in building coral reefs and in diagnosing systematic relationships in the order Scleractinia. However, molecular phylogenetic analyses revealed a paraphyly in a majority of traditional families and genera among Scleractinia showing that other biological attributes of the coral, such as polyp morphology and reproductive traits, are underutilized. Among scleractinian genera, the Euphyllia, with nine nominal species in the Indo-Pacific region, is one of the groups that await phylogenetic resolution. Multiple genetic markers were used to construct the phylogeny of six Euphyllia species, namely E. ancora, E. divisa, E. glabrescens, E. paraancora, E. paradivisa, and E. yaeyamaensis. The phylogeny guided the inferences on the contributions of the colony structure, polyp morphology, and life history traits to the systematics of the largest genus in Euphyllidae (clade V) and, by extension, to the rest of clade V. Results. Analyses of cytochrome oxidase 1 (cox1), cytochrome b (cytb), and β- tubulin genes of 36 colonies representing Euphyllia and a confamilial species, Galaxea fascicularis, reveal two distinct groups in the Euphyllia that originated from different ancestors. Euphyllia glabrescens formed a separate group. Euphyllia ancora, E. divisa, E. paraancora, E. paradivisa, and E. yaeyamaensis clustered together and diverged from the same ancestor as G. fascicularis. The 30-end of the cox1 gene of Euphyllia was able to distinguish morphospecies. Discussion. Species of Euphyllia were traditionally classified into two subgenera, Euphyllia and Fimbriaphyllia, which represented a dichotomy on colony structure. The paraphyletic groups retained the original members of the subgenera providing a strong basis for recognizing Fimbriaphyllia as a genus. However, colony structure was found to be a convergent trait between Euphyllia and Fimbriaphyllia, while polyp shape and length, sexuality, and reproductive mode defined the dichotomy better. Species in a genus are distinguished by combining polyp morphology and colony form. The cluster of E. glabrescens of the Euphyllia group is a hermaphroditic brooder with long, tubular tentacles with knob-like tips, and a phaceloid colony structure. The Fimbriaphyllia group, with F. paraancora, F. paradivisa, F. ancora, F. divisa, and F. yaeyamaensis, are gonochoric broadcast spawners with short polyps, mixed types of tentacle shapes, and a phaceloid or flabello-meandroid skeleton. Soft-tissue morphology of G. fascicularis and Ctenella chagius were found to be consistent with the dichotomy. Conclusions. The paraphyly of the original members of the previous subgenera justify recognizing Fimbriaphyllia as a genus. The integrated approach demonstrates that combining polyp features, reproductive traits, and skeletal morphology is of high systematic value not just to Euphyllia and Fimbriaphyllia but also to clade V; thus, laying the groundwork for resolving the phylogeny of clade V. © 2017 Luzon et al.